A recombinant commensal bacteria elicits heterologous antigen-specific immune responses during pharyngeal carriage - Laver, JR; Gbesemete, D; Dale, AP; Pounce, ZC; Webb, CN; Roche, EF; Guy, JM; Berreen, G; Belogiannis, K; Hill, AR; Ibrahim, MM; Ahmed, M; et al. (American Association for the Advancement of Science, 2021)
The human nasopharynx contains a stable microbial ecosystem of commensal and potentially pathogenic bacteria, which can elicit protective primary and secondary immune responses. Experimental intranasal infection of human adults with the commensal Neisseria lactamica produced safe, sustained pharyngeal colonization. This has potential utility as a vehicle for sustained release of antigen to the human mucosa, but commensals in general are thought to be immunologically tolerated. Here, we show that engineered N. lactamica, chromosomally transformed to express a heterologous vaccine antigen, safely induces systemic, antigen-specific immune responses during carriage in humans. When the N. lactamica expressing the meningococcal antigen Neisseria Adhesin A (NadA) was inoculated intranasally into human volunteers, all colonized participants carried the bacteria asymptomatically for at least 28 days, with most (86%) still carrying the bacteria at 90 days. Compared to an otherwise isogenic but phenotypically wild-type strain, colonization with NadA-expressing N. lactamica generated NadA-specific immunoglobulin G (IgG)– and IgA-secreting plasma cells within 14 days of colonization and NadA-specific IgG memory B cells within 28 days of colonization. NadA-specific IgG memory B cells were detected in peripheral blood of colonized participants for at least 90 days. Over the same period, there was seroconversion against NadA and generation of serum bactericidal antibody activity against a NadA-expressing meningococcus. The controlled infection was safe, and there was no transmission to adult bedroom sharers during the 90-day period. Genetically modified N. lactamica could therefore be used to generate beneficial immune responses to heterologous antigens during sustained pharyngeal carriage.